(untitled) (Colombia Medica, 2017)
Background:Gastroesophageal pathologies are common and multifactorial in patients with type 1 diabetes (T1DM). The evaluation with endoscopy and 24 h pH esophageal monitoring is expensive and not always available in all medical centers, especially in developing countries so more cost-effective algorithms for diagnosis are required. Clinical questionnaires are easy to apply but its utility for gastroesophageal reflux disease screening in patients with long standing T1DM must be analyzed. Objective:To evaluate the utility of the FSSG and Carlsson-Dent (CDQ) questionnaires to detect the frequency of gastroesophageal reflux disease in patients with T1DM. Methods:Analytic cross-sectional study, included 54 randomly selected patients from the T1DM clinic in our hospital. Before their routine evaluation, were asked to answer FSSG and CDQ questionnaires, classifying them as positive with a score >8 or >4, respectively. we associated and compared the clinical and biochemical characteristics between patients with or without gastroesophageal reflux detected through questionnaires. Results:Median age was 29 years (22-35), 67% were female (median of 16 years from diagnosis). In 39% of the patients FSSG was positive, CDQ was positive in 28%. A total of 71% of patients were taking medications to treat non-specific gastric symptoms. The concordance between questionnaires was 65% (p: <0.001). Those patients with tobacco consumption as well as those with poor glycemic control were more likely to score positive in either questionnaire. Conclusions:Patients T1DM had a high prevalence of gastroesophageal reflux disease. In those patients FSSG questionnaire detected a higher number of patients in comparison with CDQ.